Education at a glance interim report : Update of employment and educational attainment indicators : Update of employment and educational attainment indicators - Normandeau, S. (Organisation for Economic Co-operation and Development (OECD), 2020)
Report introduces some problems: Trends in educational attainment: 2000-2013; Upper secondary attainment and the impact of vocational education and training (VET); Labour market outcomes, by educational attainment, gender and age group; Labour market outcomes among those with low qualifications, tertiary qualifications; Differences in labour market outcomes by programme orientation at upper secondary level; Young people in education or not, and their labour market status; Young people neither in employment nor in education or training (NEET).